The stability of phycocyanin extracted from Arthrospira platensis against osmotic, acid, and temperature stress conditions - Shafieiyoun, Niloofar; Jahadi, Mahshid; Khosravi-Darani, Kianoush (Italian Journal of Food Science, 2024)
The main problem of using natural blue pigment of phycocyanin produced by Arthrospira platensis (spirulina) is its instability in the food matrix because of environmental stress. This study aimed to investigate the stability of phycocyanin under simulated conditions in food formulations against osmotic, acid, and temperature stress conditions. Thermal degradation constant (Dc) and half-life (t½) of phycocyanin extracted from Arthrospira platensis were analyzed using response surface methodology followed by a first-order kinetic reaction. The stability of phycocyanin was assessed under various temperature (50–98ºC), NaCl (0–2% w/w), and pH (4–7) values. Results showed that the stability of phycocyanin extracted from Arthrospira platensis is high at neutral pH and concentration of 1% (w/w) NaCl. The stability decreased with increase in temperature at ≥75°C. The highest stability of phycocyanin (the lowest Dc and the maximum t½ were 0.011 min-1 and 54.03 min, respectively) was achieved at 66.89°C, pH = 6.6, and NaCl of 0.40% w/w. According to processing conditions, content of phycocyanin required for a food matrix is successfully calculated by the response surface method. This research showed that phycocyanin is stable at thermal shock in a neutral pH medium and low content of NaCl (0.40% w/w).